2001
DOI: 10.1021/ma0018401
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and IR Spectroscopy of the Macromolecular Reaction of Anhydridization in a Functionalized Side-Chain Liquid Crystalline Copolymer Containing Acrylic Acid Groups

Abstract: The anhydrization reaction has been investigated in functionalized side-chain random liquid crystalline (LC) copolymers containing cyanobiphenyl mesogenic and acrylic acid (38 mol %) groups. Heat treatment of the LC copolymer at 130 °C for 5-200 h is accompanied by formation of intra-and intermolecular anhydrides and network structures causing an increase of the glass transition and clearing temperatures. The influence of annealing on the reorientational dynamics of the copolymers was investigated by broad-ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Fig. 2 also shows the 2log t m ¼ wð1=TÞ plots in the subglass state for P1 with 38( of AA (curves 4, 5) [31]. One can see that curve 4 is placed between curve 1 and 2 corresponding to the b and the g 1 processes, respectively.…”
Section: Samplementioning
confidence: 90%
See 1 more Smart Citation
“…Fig. 2 also shows the 2log t m ¼ wð1=TÞ plots in the subglass state for P1 with 38( of AA (curves 4, 5) [31]. One can see that curve 4 is placed between curve 1 and 2 corresponding to the b and the g 1 processes, respectively.…”
Section: Samplementioning
confidence: 90%
“…2. Dependences of 2log t on inverse temperature in the range of the a (6,7) and 2d (8,9) processes for P1 (6,8) and P3 (7,9) and in the range of the sub-glass processes (1-5) for PM-5-CAB (curves 1, 2) [25,27], PM-5-PhB (curves 1-3) [28,30], and for P1 with 38( AA (curves 4, 5) [31]; the points at 2log t ¼ 22:2 are the T m values obtained from the global curves. modes).…”
Section: High Temperaturesmentioning
confidence: 99%
“…Since the aliphatic spacer itself is nonpolar, its mobility can be dielectrically active only if some adjacent polar group is connected to it, for example an oxygen atom. It has been pointed out in side-chain liquid crystalline polymers [39e43] and related studies [44] that the process is observed for polymer systems with at least four spacer units. This agrees well with our observation that the g B -relaxation is only observed in polymer 7, which has six eCH 2 e spacer units.…”
Section: The G B -Processmentioning
confidence: 99%
“…It is known that the bulk (unconfined) side-chain LC polymers with cyanobiphenyl mesogen fragment and with four carbon methylene spacer reveal two local modes (called β and γ) related to the motion of mesogen and spacer, respectively. 11 Moreover, any chemical modification of chain structure (copolymer structure, H-bond, or/and network formation), which does not touch the side chain directly, does also not affect its local motion. 11 Thus, we expect to observe these local modes in the PS/LC block copolymers.…”
Section: Introductionmentioning
confidence: 99%